Mapping the long‐term influence of river discharge on coastal ocean chlorophyll‐a. Issue 5 (7th June 2022) - Auricht, Hannah; Mosley, Luke; Lewis, Megan; Clarke, Ken
Abstract: Although the potential of river discharge to support ocean productivity and marine ecosystems is known, the specifics of this relationship are poorly understood in many regions of the world. Global estimates of river flow indicate that river discharge is decreasing due to the increasing fragmentation, extraction and regulation of rivers. This likely means that the contribution of river flow to coastal productivity and water quality is changing, potentially leading to fewer and smaller magnitude ocean fertilisation events. We developed a simple analysis method, based on Earth observation data, to investigate where coastal ocean chlorophyll‐ a is most strongly influenced by river discharge. The per‐pixel spatiotemporal correlation technique (implemented using Python) correlates chlorophyll‐ a concentration (a proxy for phytoplankton biomass and indicator of primary productivity) from MODIS ocean colour data with river discharge data. The method was tested globally on 11 different rivers discharging into coastal ocean regions. Our findings suggest some of the world's largest river systems, such as the Amazon River, have zones of elevated coastal chl‐ a that extend hundreds to thousands of km from the river mouth. These findings suggest the influence of river discharge may have been underestimated in many coastal regions of the world. The method appears more effective for larger river systems discharging to ocean waters with less complex nutrient dynamics and weaker seasonal productivity patterns, most notably in temperate regions. Increasing our understanding of the specific areas influenced by river discharge, and the degree of influence over space and time, is an important step towards the improved river and coastal management. This method will increase the capacity of researchers to monitor how, when and where coastal waters are affected as river discharge continues to change into the future. Abstract : River discharge influences coastal ocean phytoplankton concentrations and thus productivity of coastal waters. We develop a method using up to 17 years of satellite imagery products to map where chl‐a (a proxy for phytoplankton biomass) in coastal waters is influenced by river discharge over the longterm. This is applied to 11 contrasting rivers on all populated continents. We find that river discharge may be far more influential on coastal water chl‐a than previously thought.